Leveraging Blockchain for Secure Data Transformation - Meet Patel; Rahul Patel; Bhunesh Varma; Sonali Sagar Kharade (Revista Electronica de Veterinaria, 2024)
Blockchain technology is rapidly transforming the landscape of secure data management and digital transformation across various industries. By leveraging its decentralized, immutable, and transparent architecture, blockchain enables secure data sharing, robust provenance tracking, and enhanced trust among participants without the need for centralized authorities64. The integration of blockchain with data transformation processes ensures data integrity through cryptographic linking and consensus mechanisms, mitigating risks of tampering and unauthorized access17. Furthermore, blockchain supports dynamic and secure data analytics by facilitating real-time monitoring and efficient data retrieval, which is crucial for applications in finance, healthcare, and supply chain management18. Despite its significant benefits, such as improved security and transparency, the adoption of blockchain for secure data transformation also presents challenges, including scalability, interoperability, and the need for advanced analytics frameworks that can operate across both on-chain and off-chain environments67. This paper provides an overview of how blockchain can be effectively leveraged for secure data transformation, highlighting its advantages, current applications, and the key challenges that must be addressed to realize its full potential in the digital era.